Development of Skala Kepuasan Kaunseling Mandatori - Abu Talib, Mansor; Juhari, Rumaya; Madon, Zainal; Rosnon, Mohd Roslan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Mandated counselling is usually associated with forced participation. Therefore, there is considerably higher likelihood of involuntary participation resulting in client’s dissatisfaction toward the counselling session. However, there exists literature that shows satisfaction and positive outcomes among mandated clients. Mandated counselling is widely practised, especially in the case of Malaysia. Thus, an instrument to measure client’s satisfaction was developed to capture the client’s perception, attitude and factors that contributed to the mandated counsel-ling satisfaction. Methods: The respondents involved in this study were adolescents in rehabilitation centres under the supervision of the Department of Social Welfare (Jabatan Kebajikan Masyarakat) aged 13 to 19 who had attended mandated counselling at least twice. The study was divided into four phases. Initially, in the first phase, the items were developed based on themes narrated by mandated clients and from the counsellor’s perspectives. Next, the initial measurement developed was tested to identify dimensions conceptualized in the instrument. Then, the reliability of the instrument was tested. In the final phase, a confirmatory factor analysis was conducted to confirm the model. Results: Findings showed a 52% of total variance was explained in the exploratory factor analysis, with an internal consistency of .919. The findings also showed a 16-item measurement with four dimensions: (a) alliance-system; (b) counselling efficacy; (c) therapeutic change; (d) counsellor-counselling effect. Conclusion: In summary, this study had identified significant factors essential in influencing satisfaction of mandated counselling clients in the Malaysian context. It is thus beneficial for counselling practitioners in their counselling work involving mandated clients.